Liver hemojuvelin protein levels in mice deficient in matriptase-2 (Tmprss6) - Krijt, Jan; Fujikura, Yuzo; Ramsay, Andrew J; Velasco, Gloria; Nečas, Emanuel (Blood cells, molecules, & diseases, 2011)
Mutations of the TMPRSS6 gene, encoding the serine protease matriptase-2, lead to iron-refractory iron deficiency anemia. Matriptase-2 is a potent negative regulator of hepcidin. Based on in vitro data, it has recently been proposed that matriptase-2 decreases hepcidin synthesis by cleaving membrane hemojuvelin, a key protein of the hepcidin-regulatory pathway. However, in vivo evidence for this mechanism of action of matriptase-2 is lacking. To investigate the hemojuvelin-matriptase-2 interaction in vivo, an immunoblot assay for liver membrane hemojuvelin was optimized using hemojuvelin-mutant mice as a negative control. In wild-type mice, two hemojuvelin-specific bands of 35kDa and 20kDa were detected in mouse liver membrane fraction under reducing conditions; under non-reducing conditions, a single band of approximately 50kDa was seen. Phosphatidylinositol-specific phospholipase C treatment confirmed binding of the detected protein to the cell membrane by a glycosylphosphatidylinositol anchor, indicating that the major form of mouse liver membrane hemojuvelin is a glycosylphosphatidylinositol-bound heterodimer. Unexpectedly, comparison of liver homogenates from Tmprss6+/+ and Tmprss6-/- mice revealed significantly decreased, rather than increased, hemojuvelin heterodimer content in Tmprss6-/- mice. These data do not provide direct support for the concept that matriptase-2 cleaves membrane hemojuvelin and may indicate that, in vivo, the role of matriptase-2 in the regulation of hepcidin gene expression is more complex.
Keywords: kationické antimikrobiální peptidy; železo; buněčná membrána; játra; Electrophoresis, Polyacrylamide Gel; signální transdukce; Membrane Proteins; Signal Transduction; Anemia, Iron-Deficiency; Iron; elektroforéza v polyakrylamidovém gelu; Tissue Extracts; Serine Endopeptidases; regulace genové exprese; anemie z nedostatku železa; dimerizace; glykosylfosfatidylinositoly; Dimerization; zvířata; myši; Antimicrobial Cationic Peptides; Mice; Phosphoinositide Phospholipase C; myši knockoutované; tkáňové extrakty; Gene Expression Regulation; Liver; serinové endopeptidasy; Male; Mice, Knockout; polymerázová řetězová reakce; Polymerase Chain Reaction; membránové proteiny; Animals; Cell Membrane; mužské pohlaví; fosfolipasa C fosfoinositidové signalizace; Glycosylphosphatidylinositols